Emerging perspectives of workplace learning - Billett, Stephen; Harteis, Christian; Eteläpelto, Anneli (Sense Publishers, 2008)
There is a growing interest in understanding learning in and through work and its relationship to what is required to be learnt for effective and productive working lives. This book offers a range of emergent perspectives based on current research on learning through and for work. The common focus among these perspectives is to understand how individuals engage in and learn through their work. This includes how they learn about, manage and respond to change in their work and develop approaches and responses to learning in, through and for their working lives. The key contribution of this book is to provide insights to support learning throughout working life in order to sustain individuals’ capacities for effective, productive and enduring working lives. Comprising 15 chapters the book offers perspectives from Finland, Germany, New Zealand and Australia and across a range of occupations and places of work. Individually and collectively these chapters make important contributions to learning about the self and agency at work and about learning work tasks. The origins of this text were a desire to bring together the work of a group of recently completed and current doctoral candidates at Jyväskylä, Regensburg and Griffith universities. This goal has been achieved here as supported by collegiate activities among the editors, contributors and their colleagues.
Keywords: formation des adultes